Synthesis, Stereochemistry and Electronic Spectroscopy of Nickel (II) Complexes with Triphenylarsine Oxide - Oliveira, L. F. C. de [UNESP]; Massabni, A. C. [UNESP] (Soc Brasileira Quimica, 1991)
Magnetic and spectroscopic data of ten complexes resulting from the interaction between Nickel(II) and triphenylarsine oxide (Ph3AsO) are described. The results are discussed in order to determine the geometry of the complexes. The preparation of the complexes [NiBr2(Ph3AsO)(2)], [NiCl2(Ph3AsO)(2)], [Ni(NO3)(2)(Ph3AsO)(2)], NiI(2 center dot)4(Ph3AsO) and [Ni(ClO4)(Ph3AsO)(4)]ClO4 was previously described in the literature. The complexes [NiBr(Ph3AsO)(4)]Br and [Ni(H2O)(6)]Br(2 center dot)4(Ph3AsO)(center dot)2(H2O) were also prepared in our laboratories and the preparation of the complexes [NiCl(Ph3AsO)(4)]Cl, [NiI2(Ph3AsO)(2)] and [Ni(NCS)(2)(Ph3AsO2] is described in the present paper. The complexes have tetrahedral, square pyramidal or octahedral geometrical forms. The crystal field parameters (Delta(t)) of the tetrahedral complexes are 4,100; 4,000; 3,920 and 3,950 cm(-1) for the complexes [NiCl2(Ph3AsO)(2)], [NiBr2(Ph3AsO)(2)], [NiI2(Ph3AsO)(2)] and [Ni(NCS)(2)(Ph3AsO)(2)], respectively. The interelectronic parameters B are 825, 805 and 795 cm-1 for the tetrahedral complexes of Cl-, Br- and I-, respectively. For the octahedral complex [Ni(NO3)(2)(Ph3AsO)(2)] the Delta(o) value is 8,330 cm(-1) and B is 823 cm(-1).
Keywords: Ni(II) complexes; triphenylarsine oxide